Plasmid-induced "hit-and-run" tumorigenesis in Chinese hamster embryo fibroblast (CHEF) cells. - Lau, C C (1985)
The Chinese hamster embryo fibroblast cell line CHEF/18 is readily transfected by plasmid DNA. In the present transfection studies with CHEF/18 cells, focus formation induced by plasmids containing the mutant human c-Ha-ras gene EJ was compared with that of control plasmids without the EJ insert. The focus-forming activity of the transfected plasmid J132, a recombinant of the Harvey murine sarcoma virus LTR and the normal human c-Ha-ras1 in pBR322, also was assessed. Foci were recovered after transfection with either pSV2gpt or pSV2neo at about 10% the frequency obtained with the EJ-containing plasmids, and J132 gave a similar frequency, all well above background obtained with salmon sperm DNA. Whereas foci from transfection with EJ-containing plasmids contained the EJ DNA, no plasmid DNA was detected in either tumorigenic or tumor-derived cells from foci transfected with pSVgpt, pSVneo, or J132. Evidence that genomic changes were induced by plasmid transfection is based on finding chromosomal aberrations in all expanded foci and tumor-derived cells examined. The results suggest the occurrence of "hit-and-run" tumorigenesis induced by transient plasmid transfection.